Breeding Insect Resistant Crops for Sustainable Agriculture 2017
DOI: 10.1007/978-981-10-6056-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Proof and Utilization of Resistance of Insect Pests in Grain Legumes: Progress and Limitations

Abstract: Major food legumes including chickpea, pigeon pea, cowpea, field pea, lentil, faba bean, black gram, green gram, and Phaseolus beans play a vital role in food, nutritional security, and sustainable crop production. Several insect pests damage grain legumes, of which Helicoverpa armigera; Maruca vitrata; Etiella zinckenella; Spodoptera litura and S. exigua; Melanagromyza obtusa; Ophiomyia phaseoli; Aphis craccivora and Bemisia tabaci; Empoasca spp., Megalurothrips dorsalis, and Caliothrips indicus; Mylabris spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 175 publications
0
3
0
Order By: Relevance
“…The overexpression of the agglutinin gene in chickpea can have a substantial impact on the survival and fertility of cowpea insects (Chakraborti et al, 2009). In addition, transgenic pigeon pea expressing Glycine max trypsin inhibitor and Cry1Ab has been developed (Sharma et al, 2006), but it does not efficiently inhibit H. armigera (Sharma et al, 2017). Transgenic chickpeas expressing an inhibitor of cowpea trypsin (Thu et al, 2003) study with an a-amylase inhibitor (Sarmah et al, 2004) demonstrated bruchid resistance.…”
Section: Transgenic Legumesmentioning
confidence: 99%
“…The overexpression of the agglutinin gene in chickpea can have a substantial impact on the survival and fertility of cowpea insects (Chakraborti et al, 2009). In addition, transgenic pigeon pea expressing Glycine max trypsin inhibitor and Cry1Ab has been developed (Sharma et al, 2006), but it does not efficiently inhibit H. armigera (Sharma et al, 2017). Transgenic chickpeas expressing an inhibitor of cowpea trypsin (Thu et al, 2003) study with an a-amylase inhibitor (Sarmah et al, 2004) demonstrated bruchid resistance.…”
Section: Transgenic Legumesmentioning
confidence: 99%
“…They are synthesized into secondary metabolites such as lignins, tannins, phytates, alkaloids, quinines, phenolic acids, saponins and flavonoids found in plant structures such as seed coat and integuments and secrete antinutritional factors such as arcelins, trypsin inhibitors, enzyme inhibitors, lectins, vicilin, cyanogenic glycosides, phytic acid and phaseolin which acts as repellents and feeding inhibitors (Panda et al 1995). This mechanism leads to reduced larval growth, increased larval mortality, and decreased pupal weights, prolonged larval and pupal development periods, low pupation, low fecundity rates and decreased egg viability (Sharma et al 2017;War et al 2013).…”
Section: Antibiosismentioning
confidence: 99%
“…However, the unpredictability in pigeonpea production due to poor genetic background and damage by insect pests and diseases limits the seed yield of this crop. Under storage conditions, bruchids, C. chinensis and C. maculatus crusade extensive losses to all the food legumes worldwide (Sharma et al, 2017) and causing 40-50% losses of pulses in storage (Gosh and Durbey, 2003). Keeping this in view, the present research focuses mainly on the possibilities of exploring biochemical sources of resistance to bruchids in cultivated as well as wild relatives of pigeonpea.…”
Section: Introductionmentioning
confidence: 99%